Using an online engagement framework to redesign the learning environment for higher education students: A design experiment approach - Melissa Fanshawe; Alice Brown; Petrea Redmond (Online Learning)
With more higher education courses being offered online, the design of the learning environment is an essential component of the educational experience. However, not all online learning environments facilitate student engagement. This paper describes the redesign of two online Initial Teacher Education courses in a regional university, using the Online Engagement Framework (OEF) for higher education. Following a design experiment approach, we audited the online course components in the previous offerings and redesigned the courses considering the five dimensions of online learning. To understand the effectiveness of the redesign, we analysed student feedback from 24 course offerings along with course analytics. We identified significant increased student engagement and student data showed they highly valued cognitive, behavioural and emotional elements within online courses. The findings suggest that the OEF could be used to guide the redesign of learning environments to forefront student engagement.